Pengaruh Tingkat Kesejahteraan, Komunikasi, Dan Pengalaman Kerja Terhadap Semangat Kerja Karyawan Pt. Inti Buana Permai Denpasar Bali - Widiartha, Putu Nanda (E-Jurnal Manajemen, 2013)
Morale has great significance for the survival of the company, with high morale, it will cause the high sense of concern for the achievement of corporate goals. That employees have high morale, an organization needs to consider the factors that affect morale. See any indication as it has been presented, the research aimed to investigate the influence together, and partial (independent) variables between the level of welfare, communication and work experience of the employee morale at PT. Inti Buana Permai Denpasar Bali. Summing up the results of F count (71.249)> F table (2,76). Variable levels of well-being, communication and work experience with a partially significant employee morale PT. Denpasar Bali Buana Permai core, this fact can be seen in the results of the t test, in which the level of welfare for the variable t (5,026)> t table (1.684), for t communication variables (3.403)> t table (1.684), and so is work experience variable t (2.431)> t table (1.684). Keywords: morale, welfare, communication, work experience.